The Effect Of Head Massage Therapy On Blood Pressure In Hypertension Patients Pre Operations In The Home Outpatient Unit Eye Soreness Invitation Surabaya - Anik Nuridayanti; Dewi Retno Puspitosari; Nurhidayah (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Hypertension is one of the main causes of mortality and morbidity in Indonesia, found at various levels of health facilities so that preventive and curative efforts are needed, one of which is the application of head massage therapy. The purpose of this study was to determine the effect of head massage therapy on patients with preoperative hypertension at the Undaan Eye Hospital, Surabaya. The research design used is Pre-Experimental Design One Group Pre – Post Test Design. The population of this study were 35 respondents. The Instruments used are SPO head massage, sphygmomanometer, and observation sheet. The analysis used the Paired Sample T Test statistical test with a significance level of 0.05. The results showed that the value of p = 0.000 <0.05 so that H0 was Rejected, meaning that there was an effect of Head Massage Therapy on the blood pressure of hypertensive patients. The results of blood pressure before treatment Were mostly grade 2 as many as 26 respondents (81%) while after treatment most Were grade 1 as many as 17 respondents (53%).With this research, it is hoped that head massage therapy can be applied to patients with hypertension in health services and it is hoped that further research can develop a better theory, duration of administration and design.